Application of congestion avoidance mechanism in multimedia transmission over mesh networks. (29th July 2019) - Zhu, Biaokai; Zhao, Jumin; Li, Deng-Ao; Bai, Ruiqin
The unreliable nature and shared multi-media of multi-hop communications cause the deployment of multi-media applications in wireless mesh network (WMN) a thorny problem. For instance, video is usually compressed into a group of frames before transmission, resulting in unrecoverable destruction during the display process. The importance of different frames' type is quite different. However, they are considered as same in most existing WMNs. In this paper, we propose a novel Congestion Avoidance Mechanism for multimedia transmission over 802.11e mesh networks. In our mechanism, we added priority for video packets. According to the significance of frames, we proposed an adaptive mechanism involves the mapping of H.264 video packets to appropriate access categories in IEEE 802.11e standard. Simulation results show that our mechanism improves quality of service (QoS) of multimedia transmission.